Deconstructing sustainable rubber production: contesting narratives in rural Sumatra. Issue 2 (3rd May 2020) - Otten, Fenna; Hein, Jonas; Bondy, Hannah; Faust, Heiko
ABSTRACT: The growing demand for natural rubber is increasingly threatening biodiversity and forest ecosystems. Recently, the French Michelin Group started a cooperation with the World Wide Fund for Nature (WWF) to establish environmentally and socially sustainable 'model' rubber plantations in Sumatra and Kalimantan, Indonesia. The framing of Michelin's tyre production as 'eco-friendly' and their purported 'sustainable' rubber cultivation contradict with statements by villagers living around Michelin's plantation in Jambi Province, Sumatra, who are reporting environmental destruction and land tenure conflicts. Conceptually, we build on political ecology and critical human geography perspectives to identify conflicts and ambiguities related to sustainability claims, deforestation and dispossession. Empirically, we draw on qualitative research in a village affected by the plantation. We confront and deconstruct the discursive framing of sustainable rubber production with our empirical findings. We show how the plantation restricts access to land and instead of providing additional income, is actually limiting development opportunities.